Socio-spatial stratification of housing tenure trajectories in Sweden – A longitudinal cohort study. (June 2022) - Borg, Ida; Kawalerowicz, Juta; Andersson, Eva K.
Abstract: Individuals tend to be most mobile when they are between 20 and 40 years of age. This pattern is relatively stable across regions and over time. For geographical mobility, less is known about their transitions between different types of housing and tenure forms. In Sweden, households may select between, principally, three different types of tenure forms, each often coupled with a specific housing type. Households may rent from either public companies (municipality owned) or private landlords in multifamily dwellings, households may own their single-family house privately, or they can cooperatively own a multifamily house as a tenant-owner in an apartment. Yet we lack knowledge of which tenure trajectories individuals tend to follow during their most mobile years, and we also lack knowledge about which factors determine tenure trajectories. Our sample consist of individuals who in 1995 were aged 18–25 and who left their parental house between 1994 and 1995. This study tracks their tenure trajectories for 21 consecutive years starting in 1995 until 2015. The cohorts in our sample were the first who encountered the conditions on the deregulated housing market that are still in place in Sweden today. We followed these cohorts until they were between 39 and 46 years old and used sequence analysis to classify tenure trajectories. One result that stands out is the outstanding and increasing emphasis on home ownership in our sample, quite unlike the traditional picture of the Swedish housing market. Additionally, we found that resources in a broad sense and spatial context have a great impact on the type of trajectory individuals follow. Highlights: The majority of those who moved from parental home between 1994 and 1995 tend to follow home owning trajectories. We find five different routes into stable owner occupied housing. We find three types of trajectories were rental housing is a long-term option. Entering the owner occupied housing sector is stratified according to socio-economic resources and characteristics of parental home location.